Proof: Get New State 16
Let's prove the following theorem:
if expression state at time 16 = "return", then expression state at time 17 = "iterate_args"
Proof:
Given
1 | expression state at time 16 = "return" |
---|
# | Claim | Reason |
---|---|---|
1 | expression state at time (16 + 1) = "iterate_args" | if expression state at time 16 = "return", then expression state at time (16 + 1) = "iterate_args" |
2 | 16 + 1 = 17 | 16 + 1 = 17 |
3 | expression state at time (16 + 1) = expression state at time 17 | if 16 + 1 = 17, then expression state at time (16 + 1) = expression state at time 17 |
4 | expression state at time 17 = "iterate_args" | if expression state at time (16 + 1) = expression state at time 17 and expression state at time (16 + 1) = "iterate_args", then expression state at time 17 = "iterate_args" |
Comments
Please log in to add comments